2005
DOI: 10.1161/01.cir.0000164201.40634.1d
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bone Morphogenetic Protein-2 Expression in Endothelial Cells

Abstract: Background-Recent studies suggest that bone morphogenetic protein-2 (BMP-2), a transforming growth factor-␤ superfamily member cytokine, plays an important role both in vascular development and pathophysiological processes, including endothelial activation that is likely to contribute to the development of coronary atherosclerosis, yet the factors that regulate arterial expression of BMP-2 are completely unknown. We tested the hypothesis that BMP-2 expression in endothelial cells is governed by an H 2 O 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
103
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(112 citation statements)
references
References 37 publications
9
103
0
Order By: Relevance
“…Several studies show an important role of the NF-κB pathway in mediating vascular cell osteogenic responses (42). Although we have reported that NF-κB and ERK1/2 mediate induction of BMP-2 and ALP in human AVICs (12), we now note that recombinant IL-37 suppresses NF-κB phosphorylation and DNA-binding activity and inhibits ERK1/2 phosphorylation in human AVICs exposed to LPS, Pam3CSK4, or oxLDL.…”
Section: Il-37 Suppresses Avic Osteogenic Responses Through Inhibitiomentioning
confidence: 56%
“…Several studies show an important role of the NF-κB pathway in mediating vascular cell osteogenic responses (42). Although we have reported that NF-κB and ERK1/2 mediate induction of BMP-2 and ALP in human AVICs (12), we now note that recombinant IL-37 suppresses NF-κB phosphorylation and DNA-binding activity and inhibits ERK1/2 phosphorylation in human AVICs exposed to LPS, Pam3CSK4, or oxLDL.…”
Section: Il-37 Suppresses Avic Osteogenic Responses Through Inhibitiomentioning
confidence: 56%
“…An interesting, albeit at this point speculative, possibility is that the signals controlling growth of the mesentery are themselves under control of physical forces, creating a feedback loop. There is evidence in other systems that Bmp2 expression can be modulated by tension (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endothelial cells are major targets of proinflammatory cytokines such as TNF-α and interleukin-1β (IL-1β) and these proinflammatory cytokines regulate BMP-2 expression in pathological conditions. For example, studies by Csiszar et al showed that TNF-α increased BMP-2 expression in endothelial cells [19,27]. Thus, under inflammatory conditions, BMP-2 released from endothelial cells may act on adjacent SMC, induce osteochondrogenic differentiation and result in calcification in the arterial tree.…”
Section: Discussionmentioning
confidence: 99%